Part III, Free Actions of Compact Quantum Groups on C*-Algebras - Schwieger, K.; Wagner, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We study and classify free actions of compact quantum groups on unital C∗-algebras in terms of generalized factor systems. Moreover, we use these factor systems to show that all finite coverings of irrational rotation C∗-algebras are cleft.